Strategi Pondok Tahfidz Ustadz Mahyuddin dalam Meningkatkan Motivasi Belajar Al-Qur’an Usia Dewasa dan Lansia - Abdul Kodir Jailani; Nurfarida Deliani; Juliana Batubara (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Qur'an is the word of Allah Swt which was revealed to the Prophet Muhammad Saw through the intermediary of the angel Gabriel which was conveyed to his people mutawatir and reading it is worth worship. Learning the Qur'an must be continuous throughout life, including among adults and the elderly. To learn the Qur'an for adults and the elderly, there needs to be high motivation in order to have a high enthusiasm for learning the Qur'an. This study aims to determine the strategy of Pondok Tahfidz Ustadz Mahyuddin (PTUM) in increasing the motivation to learn the Qur'an for adults and the elderly. This research was conducted at Pondok Tahfidz Ustadz Mahyuddin (PTUM) Bungo Mas Housing Phase III Koto Panjang Ikur Koto Village, Koto Tangah District, Padang City using a descriptive qualitative approach. The main instrument of this qualitative research is the researcher himself and data collection techniques are carried out by interview, observation and documentation, Data analysis in this study is inductive. The results of this study indicate that through various strategies that have been carried out by Pondok Tahfidz Ustadz Mahyuddin (PTUM) has succeeded in increasing the motivation to learn the Qur'an of adult and elderly students marked by their enthusiasm in participating in Qur'anic learning. The implication of this research is to broaden the understanding of learning strategies in increasing the motivation to learn the Qur'an for adults and the elderly.